(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2023)
Mary Wollstonecraft’s A Vindication of the Rights of Woman (1792), is nowadays presented as a foundational text for modern feminism. Its rapid rendering into European languages such as French and German contrasts with the late translation into Spanish, which was not published until 1977. Nevertheless, the twenty-first century has witnessed a renewed interest in the figure of Wollstonecraft and her role as a precursor of the first feminist wave in Europe. Within this framework, this study examines Wollstonecraft’s public reception in Spain through contemporary (re)translations of her work. For this purpose, attention is paid to translations into Spanish and other co-official languages published during the first two decades of the twenty-first century, as well as the author’s public reception in Spanish newspapers. This research, thus, attests to the recent process of recovery of Wollstonecraft’s work in Spain and underscores her iconic role in contemporary local and international feminist discourses.